Acceleration of Technology Adoption withing Firms - Philipp Koellinger; Christian Schade (Tinbergen Institute, 2008)
This paper studies the diffusion of multiple, related technologies among firms. The results suggest an endogenous acceleration mechanism of technology adoption: The more advanced a firm is in using a particular set of technologies, the more likely it is to adopt additional, related technologies. We show that such a mechanism can occur under fairly general circumstances. If firms are not ex ante identical, the endogenous acceleration mechanism suggests a growing divergence in technological endowment of firms in the early phases after the emergence of a new technological paradigm. The theoretical predictions are tested with a dataset that records the adoption times of various e-business technologies in a large sample of firms from 10 different industry sectors and 25 European countries. The results show that the probability to adopt strictly increases with the number of previously adopted e-business technologies. Evidence for a growing digital divide among the companies in the sample is demonstrated for the period from 1994-2002.
Keywords: O33; O14; 330; Technology adoption; technological change; complementarity; hazard rate model; IT; Technologiewahl; Innovationsdiffusion; E-Business; Unternehmenserfolg; Europa